2014
DOI: 10.1308/003588414x14055925058878
|View full text |Cite
|
Sign up to set email alerts
|

Parental perception of acute scrotal pain in children

Abstract: INTRODUCTION Acute scrotal pain (ASP) remains one of the more common urological emergencies in the paediatric age group. Acute testicular torsion is the only true urological emergency, where delay in presentation or management can lead to loss of the affected testicle. Since prompt presentation, diagnosis and treatment are critical for testicular salvage, multiple patient and hospital specific factors may influence orchidectomy rates. Parental awareness of the sequelae of ASP may be a significant factor in del… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
24
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 13 publications
4
24
0
Order By: Relevance
“…17 Another prospective study of 76 boys by Ubee et al demonstrated similar findings that the majority of parents did not fully appreciate the implications of acute scrotal pain. 18 This correlates with our findings as well, and reiterates the need for education in this area.…”
Section: Discussionsupporting
confidence: 92%
“…17 Another prospective study of 76 boys by Ubee et al demonstrated similar findings that the majority of parents did not fully appreciate the implications of acute scrotal pain. 18 This correlates with our findings as well, and reiterates the need for education in this area.…”
Section: Discussionsupporting
confidence: 92%
“…While the time interval between symptoms and first medical assessment, i.e. presentation delay, rests upon the patient’s awareness of the disease and medical care availability ( 11 - 13 ), delays from this first assessment until evaluation at the treating institution have been associated with the first examining physician’s clinical diagnosis and subsequent action, such as imaging studies orders and inter-hospital patient referral and transfer ( 14 - 16 ). This information, however, comes from economically advanced countries, and although one may postulate that similar associations should also be observed in emerging countries, region-specific data is necessary to ascertain not only the existence but also the magnitude of these associations.…”
Section: Introductionmentioning
confidence: 99%
“…Others have reported adolescent male patients and their parents are universally unaware of testicular pathology unique to their age group, including the need to seek emergent attention for painful and painless testicular swelling. [5][6][7][8] Need for education additionally applies to boys with undescended testes whose presentations of testicular torsion are likely to be atypical. 20 Our results are limited by inherent restrictions of retrospective review, including ability to report association but inability to prove 1 symptom profile or patient characteristic caused a delay in presentation or misdiagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 To date, research and quality care initiatives have focused on improving the accuracy of diagnosis and accelerating care pathways. 3,4 Although isolated surveys have examined patient and parental awareness of acute scrotal pathology unique to adolescence, [5][6][7][8] to our knowledge other factors associated with delay in presentation after onset of symptoms have not been reported. As the vast majority of delayed presentations of testicular torsion undergo orchiectomy, knowledge of factors affecting acute vs delayed presentation directly impacts testicular salvageability.…”
mentioning
confidence: 99%